Communication aspects of mergers with multiculturalism risks - Gősi, Mariann (Studia Mundi – Economica, 2015)
Merger is defined as a process where two or more companies unite their resources to develop a new entity. This decision is usually mutual between both firms. The previous characteristics change significant before the merger, whether they are homogeneous even before the merger. The merger can be imagined many alternative ways. The aim of the study to describe the theoretical aspects of the merger process and its communications risks in the frame of change evaluation, and to present consistent, static and dynamic modeling based on these point of view. That allows significantly the increasing support of planning processes. Know how is suitable for foundation of startups interested in consulting.